emahami Transisi Identitas Fisika: Tinjauan Sistematis tentang Pengaruh Gender dan Sosial-Budaya pada Mahasiswa dan Calon Guru Fisika - Anjani, Melly Yuni; Hidayat, Arif; Munfaridah, Nuril (EduFisika: Jurnal Pendidikan Fisika, 2026)
The aim of this study is to provide a comprehensive overview of the literature on physics identity transitions and to examine how gender and sociocultural contexts influence the formation and transformation of these identities. Additionally, this study will identify the methodologies used in previous studies. A systematic literature review (SLR) was conducted following PRISMA guidelines. Relevant articles were retrieved from three major databases (Scopus, ERIC, and Google Scholar) published between 2019 and 2025. Nine studies were selected for analysis using thematic analysis to identify contextual, social, and methodological patterns. The findings suggest that physics identity is shaped by the interaction of internal factors, such as interest, competence/performance, and self-efficacy, as well as external factors, including recognition, sense of belonging, and community support. The results also show that identity construction is not socially neutral but influenced by gender stereotypes, masculine norms, and sociocultural contexts that shape individual participation and legitimacy. Methodologically, the literature is still dominated by cross-sectional quantitative approaches, which limits the understanding of identity transition as a dynamic process. This study confirms that strengthening physics identity depends not only on the individual but also on the support of an inclusive, relational, community-based learning environment. It also encourages the development of more contextual, longitudinal research that uses a mixed methods approach.